Pengaruh E-Wallet dan Gaya Hidup Terhadap Perilaku Konsumtif Mahasiswa dengan Kontrol Diri Sebagai Variabel Intervening - Romansyah Sahabuddin; Azlan Azhari; Kartika Kartika; Nurul Annisa Septyanti; Muh. Ahimsyah; Dhinda Dwi Maharani (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
. This study aims to analyze the effect of e-wallet usage and lifestyle on student consumer behavior, with self-control as an intervening variable. The approach used is associative quantitative, with a sample of 155 student e-wallet users in Makassar City selected using purposive sampling technique. Data were collected through online questionnaires and analyzed using Structural Equation Modeling (SEM) based on LISREL 8.50. The results of the study indicate that e-wallet usage and lifestyle have a significant effect on student consumer behavior, both directly and indirectly. Self-control has been shown to be able to reduce the tendency of consumer behavior, thus becoming an important factor in managing the negative impacts of transaction digitalization and lifestyle changes among students. These findings provide implications for the development of personal financial management strategies and increasing digital financial literacy in the modern era.